Examining interactivity in synchronous virtual classrooms - Florence Martin (Athabasca University Press, 2012)
Interaction is crucial to student satisfaction in online courses. Adding synchronous components (virtual classroom technologies) to online courses can facilitate interaction. In this study, interaction within a synchronous virtual classroom was investigated by surveying 21 graduate students in an instructional technology program in the southeastern United States. The students were asked about learner-learner, learner-instructor, learner-content, and learner-interface interactions. During an interview, the instructor was asked about strategies to promote these different forms of interaction. In addition, the academic, social, and technical aspects of interactions were examined in three course archives using Schullo’s (2005) schema. Participants reported that the Wimba interface was easy to use and that various features, such as text chat and the webcam, facilitated interaction among the students and with the instructor in the virtual classroom. The importance of students’ ability to receive immediate feedback and their experience as presenters was highlighted across the various kinds of interaction. The instructor’s teaching style and visual presence were instrumental in engaging students with the content. The results suggest that student interaction, and hence learning, was aided by the live communication that occurred through the virtual classroom. This study has implications for those who are considering adopting virtual classroom technologies for their online or blended teaching.